2008
DOI: 10.1111/j.1523-5378.2008.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Helicobacter pylori Infection in Chinese Populations

Abstract: Background: The prevalence of Helicobacter pylori is higher in developing countries. The aim of this study was to investigate the prevalence and risk factors of H. pylori infection in areas with high prevalence of gastric cancer in Jiangsu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
79
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 55 publications
17
79
4
4
Order By: Relevance
“…In our investigation, the overall seroprevalence in humans was relatively high (44.4%) ( Table 3). This was somehow higher than results shown in previous studies from other countries: United Kingdom (27.6%) [28], Australia 15.4% [29], and United State (36.3%) [30], while it was lower than reports in Uganda (87%) [31], China (62%) [32], and neighboring Arabian countries, mainly Libya (94%) [33] and Sudan (65%) [34]. The diversity of crowding, socioeconomic status, and environmental and hygiene factors may play an important role in increased rates of H. pylori infection in developing countries.…”
Section: Discussioncontrasting
confidence: 69%
“…In our investigation, the overall seroprevalence in humans was relatively high (44.4%) ( Table 3). This was somehow higher than results shown in previous studies from other countries: United Kingdom (27.6%) [28], Australia 15.4% [29], and United State (36.3%) [30], while it was lower than reports in Uganda (87%) [31], China (62%) [32], and neighboring Arabian countries, mainly Libya (94%) [33] and Sudan (65%) [34]. The diversity of crowding, socioeconomic status, and environmental and hygiene factors may play an important role in increased rates of H. pylori infection in developing countries.…”
Section: Discussioncontrasting
confidence: 69%
“…Asian-Pacific guidelines on gastric cancer prevention recommend screening for and eradicating H. pylori in high-risk populations (Fock et al, 2009). Since 2003, numerous studies have also been conducted to examine the prevalence of H. pylori in healthy people in different regions of China, with reported prevalence ranging from 40% to 81% (Shi et al, 2008). In our studies, we found 41.5% of migrant workers were infected with H. pylori.…”
Section: Discussionsupporting
confidence: 50%
“…No significant association was found between H. pylori infection and gender, but higher frequency of infection was observed among men in the current study. Similar observations have been reported previously in China (14). The highest frequency of H. pylori was observed in the fourth decade of life (39%) and lowest frequency (28%) was found in patients who had already completed their fifth decade of life.…”
Section: Discussionsupporting
confidence: 91%